Uji Efektifitas Jamur Entomopatogen Beauveria bassiana dan Metarhizium anisopliae terhadap Kepik Hijau (Nezara viridula L.) (Hemiptera ; Pentatomidae) pada Tanaman Kedelai (Glycine max L.) di Rumah Kasa - Suprayogi Suprayogi; Marheni Marheni; Syahrial Oemry (Jurnal Agroekoteknologi, 2015)
The objective of the research was study of  the effectivity test  of  fungi entomopathogen    Beauveria  bassiana  and  Metarhizium anisopliae on different conydia densities to infect the rodentadult green stink bug  (Nezara viridula L.) This research was conducted at the screen house Facultyof Agriculture, University of North Sumatra, from Desember 2013 until Mei 2014. This researchusing Randomized Block Design non factorial with 7 treatments (control, suspension  M. anisopliaewith conydia density 107/70 ml water, suspension M. anisopliae with conydia density 10/70 mlwater, suspension M. anisopliae with conydia density 109/70ml water, suspension  B. bassiana withconydia density 107/70 ml water, suspension B. bassiana with conydia density 10/70 ml water,suspension B. bassiana  with conydia density 109/70 ml water) with three replications. The results showed that fungi entomopathogen B. bassiana and M. anisopliae affected significantly topercentage of mortality, percentage of natalitas, and soy production. The best result for thepercentage of mortality was N3 (suspension  M. anisopliae with conydia density 10/70 ml water)with 94.44%, The highest percentage of  natalitas was  Nwith 96.40%, The highest soy productionwas N3 (suspension  M. anisopliae with conydia density 100 9/70 ml water) with 20.77 gr/polibeg/6crop.Key words:  Glicyne  max L.,  Nezara viridula L.,  Metarhizium anisopliae, Beauveria bassiana 898